Ang ating huntahanan a rebranding campaign for museo ng Baliwag to raise the awareness of 9 to 13-year-old Baliwagenyos of Baliwag's history, culture and heritage - Saavedra, Maria Fatima B.
Baliwag is a first-class municipality in the province of Bulacan, a beautiful town with its landscape, traditions, history, and people. Baliwag is home to the buntal hat (Balibuntal), imbuteladen furniture and the longest and grandest Holy Week Lenten procession in the Philippines. One such way to see and experience Baliwag is through its official town museum, Museo ng Baliwag, the mandate of which is to "promote and build the heritage, and artistic, historical and cultural colletion" of Baliwag, as stated in executive order no. 30 of current Mayor Ferdinand Estrella. Nonetheless, only a few Baliwagenyos have visited and revisited the museum since its opening in 2015. Most Baliwagenyos are not aware of the history and heritage of their town. Apart from differences in individual interests, the museum lacks a good visual communication strategy in order to be more inviting and keep a steady attendance and increase, thereof. There is also a lack of sustainability in the promotions done by the museum. Particularly, some young Baliwagenyos have visited the museum, but these visits are not frequent. The youth will also rather focus their attention on instant entertainment than visit the museum, or any historical landmark to learn about Baliwag. To respond to the endeavor of the town towards urbanization, Honorable Ferdinand Estrella signed an executive order for the creation of the town museum. Additionally, the National Museum has named Museo ng Baliwag an important cultural property. The museum also awaits funding from Tourism Infrastructure and Enterprise Zone Authority (TIEZA) for major restoration. There is already an official plan for a renovation to take place on the last quarter of 2019. This plan was initiated by the museum curator, Mrs. Susana Villanueva. The museum's new program will include permanent and temporary exhibits of Baliwag's local traditions, arts, history, and heritage. It has also proposed educational programs so that the visitors may learn about Baliwag in a wide array of modalities and appreciate the town. Ultimately, the goal is to increase museum visitation and recurrent visits. In line with this, the proponent recommends a rebranding campaign for Museo ng Baliwag, to inform and further engage the Baliwagenyos about their town's heritage, history and culture. This will focus on 9 to 13-year-old Baliwagenyos, who make up majority of the town's population (in general, youth under 26 years old). This age group was chosen as young minds are good grounds for cultivation of information especially about the town's history and culture as ideas can easily impressed on them. This rebranding campaign aims to create and image that Museo ng Baliwag is home to the Baliwagenyos, and a place where they can meet, and engage in history, culture and tradition. According to the data gathered by the proponent, this will also help reinforce their self-identity, confidence, and love of nation. The educators and parents will be target markets as well (secondary and tertiary, respectively). They will be guides to the children as they go in and out of the museum to ensure that learning outcomes are met. The rebranding campaign will focus on the concept of Knowing Your Home which aims to reach out to a young audience. This campaign will aim to produce materials to engage the children into a fun learning process regarding the history, culture and traditions of Baliwag. While the museum is of the Spanish colonial era, strategies will be used to engage young children into learning through an audio-visual and kinetic approach such as the creation and dissemination of posters, brochures, activity books, maps. digital application/hypermedia (can be accessed in the museum premises), to name a few.